Amiodarone Provides Long-Lasting Local Anesthesia and Analgesia in Open-State Mouse Nociceptors - Kotoda, Masakazu; Matsuoka, Toru; Wada, Keiichi; Jayakar, Selwyn; Ino, Hirofumi; Kawago, Koji; Kumakura, Yasutomo (Frontiers in Pharmacology, 2022)
Local anesthetics with long-lasting effects and selectivity for nociceptors have been sought over the past decades. In this study, we investigated whether amiodarone, a multiple channel blocker, provides long-lasting local anesthesia and whether adding a TRPV1 channel activator selectively prolongs sensory anesthetic effects without prolonging motor blockade. Additionally, we examined whether amiodarone provides long-lasting analgesic effects against inflammatory pain without TRPV1 channel activator co-administration. In the sciatic nerve block model, 32 adult C57BL/6J mice received either bupivacaine, amiodarone with or without capsaicin (a TRPV1 agonist), or vehicle via peri-sciatic nerve injection. Sensory and motor blockade were assessed either by pinprick and toe spread tests, respectively. In another set of 16 mice, inflammatory pain was induced in the hind paw by zymosan injection, followed by administration of either amiodarone or vehicle. Mechanical and thermal sensitivity and paw thickness were assessed using the von Frey and Hargreaves tests, respectively. The possible cardiovascular and neurological side effects of local amiodarone injection were assessed in another set of 12 mice. In the sciatic nerve block model, amiodarone produced robust anesthesia, and the co-administration of TRPV1 agonist capsaicin prolonged the duration of sensory blockade, but not that of motor blockade (complete sensory block duration: 195.0 ± 9.8 min vs. 28.8 ± 1.3 min, F (2, 21) = 317.6, P < 0.01, complete motor block duration: 27.5 ± 1.6 min vs. 21.3 ± 2.3 min, F (2, 22) = 11.1, P = 0.0695). In the zymosan-induced inflammatory pain model, low-dose amiodarone was effective in reversing the mechanical and thermal hypersensitivity not requiring capsaicin co-administration (50% withdrawal threshold at 8 h (g): 0.85 ± 0.09 vs. 0.25 ± 0.08, P < 0.01, withdrawal latency at 4 h (s) 8.5 ± 0.5 vs 5.7 ± 1.4, P < 0.05). Low-dose amiodarone did not affect zymosan-induced paw inflammation. Local amiodarone did not cause cardiovascular or central nervous system side effects. Amiodarone may have the potential to be a long-acting and nociceptor-selective local anesthetic and analgesic method acting over open-state large-pore channels.